PERBEDAAN H-REFLEKS PADA PASIEN DIABETES MELITUS DENGAN ULKUS KAKI DIABETIK DAN TANPA ULKUS KAKI DIABETIK - YULIAWATI, ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The prevalence of diabetes mellitus (DM) is increasing dramatically worldwide. As the prevalence of diabetes increases, the prevalence of long-term diabetes-related complications is also likely to increase. One of the long-term complications of diabetes mellitus in the lower extremities is a diabetic foot ulcer. Diabetic foot ulcers can be prevented with the identification and management of risk factors. One of the main risk factors underlying the development of diabetic foot ulcers is neuropathy. H-reflex is electrodiagnostic studies that can be used for the identification and diagnosis of diabetic neuropathy. But, H-reflex study in patients with diabetic foot ulcers is still limited and there has been no study comparing examination of the H-reflex in diabetic patients with diabetic foot ulcers and diabetic patients without diabetic foot ulcers. This study used cross sectional design. The population of the subject comprised of 35 diabetic patients with diabetic foot ulcers and 35 diabetic patients without diabetic foot ulcers. H-reflex examination were done in both of group to obtain the H-reflex parameters such as H latency, H amplitude, M latency and M amplitude. Comparison of the H-reflex parameters showed statistically significant differences in all parameters of the H-reflex including H latency, H amplitude, M latency and M amplitude between diabetic patients with and without diabetic foot ulcers. The H Latency in diabetic patients with diabetic foot ulcers is 122% of the normal value and 108% of normal value in diabetic patients without diabetic foot ulcers. The H amplitude in diabetic patients with diabetic foot ulcers was 28.3% of the normal value and 12,1 % of the normal value in diabetic patients without diabetic foot ulcers. M Latency in diabetic patients with diabetic foot ulcers is 113% of the normal value and 97% of the normal value in diabetic patients without foot. The conclusion of this study are the H and M latency in patients with diabetic foot ulcers were more prolonged than DM patients without ulcers. The H and M amplitude were more decreased in diabetic patients with diabetic foot ulcers than without ulcer.